Inclusive Education and Social Justice: Promoting Equal Learning Opportunities for All - Bhowmik, Khokan; Maiti, Sujay (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
Inclusive education has become a fundamental principle in modern educational systems, aiming to ensure that all learners, regardless of their social, economic, cultural, or physical differences, have equal access to quality education. The concept is closely associated with social justice, which promotes fairness, equality, and equal participation in society. This paper examines the relationship between inclusive education and social justice and highlights the importance of providing equal learning opportunities for all students. The study reviews relevant literature to understand the role of inclusive practices in reducing educational inequalities and promoting participation among diverse learners. The findings indicate that inclusive education enhances academic achievement, social interaction, and mutual respect among students. It also emphasizes the role of teachers, educational institutions, and policy frameworks in implementing inclusive practices effectively. The paper concludes that strengthening inclusive education through teacher training, supportive policies, and improved learning environments is essential for achieving social justice and equitable education systems.